Henstock-Kurzweil Integral Transforms - Salvador Sánchez-Perales; Francisco J. Mendoza Torres; Juan A. Escamilla Reyna (International Journal of Mathematics and Mathematical Sciences)
We show conditions for the existence, continuity, and differentiability of functions defined by , where is a function of bounded variation on with .